ROLE OF SELF-EFFICACY IN E-LIBRARY USAGE AMONG STUDENTS OF A PUBLIC UNIVERSITY IN MALAYSIA - Ramayah, T.; Aafaqi, Bushra (Malaysian Journal of Library and Information Science, 2004)
This study looked at the influence of self-efficacy on e-library usage by 704 university students from four different schools in a Malaysian public university -, School of Humanities, School of Mass Communication, School of Chemistry and School of Biology. The results of the study suggest that self-efficacy has a significant direct impact on perceived usefulness and perceived ease of use when predicting e-library usage. Results also suggest that self-efficacy, perceived ease of use and perceived usefulness have direct significant impact on e-library usage. The results further indicate that perceived ease of use fully mediates self-efficacy when explaining e-library usage and perceived usefulness fully mediates perceived ease of use when predicting e-library usage.